Hubungan Tekanan Darah dan Obesitas Sentral dengan Kadar Gula Darah pada Lansia Penderita Diabetes Melitus Tipe II - Savitri Gemini; Regina Natalia (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels or hyperglycemia which over time causes serious damage to the heart, blood vessels, eyes, kidneys, and nerves. This study aims to determine the relationship between blood pressure and central obesity with blood glucose levels in elderly people with type II diabetes mellitus.Methods: This type of research includes analytical observational research using a cross sectional design. The sample in this study amounted to 61 people using non probability with purposive sampling technique. The research was conducted in March 2023 and the research was conducted at the Sei Langkai Health Center, Batam City. In this study the variables to be studied are blood pressure, central obesity, and blood sugar levels. For unvariate analysis, the research results of each variable are presented in a frequency distribution and bivariate analysis of statistical tests used in this study is the chi square test.Results: The results of the study of 61 elderly people mostly experienced a moderate increase in blood pressure with a moderate blood glucose level category, namely (26.2%), of 61 elderly people mostly experienced central obesity with poor blood glucose levels, namely (45.9%). The results of the analysis using chi-squere showed that there was a significant relationship between blood pressure and blood glucose levels with a p-value of 0.000 <0.05, and central obesity with blood glucose levels in the elderly with a p-value of 0.001 <0.05.Conclusion: Diabetes mellitus control efforts are one of the minimum services that must be carried out by local governments. With this guarantee, it is hoped that all patients with diabetes mellitus can be controlled and receive good management to avoid complications and death themselves and can reduce the cost burden due to diabetes mellitus and its complications.